Synthesis and photovoltaic properties of low band gap quarterthiophenes-alt-diketopyrrolopyrroles polymers having high hole mobility - Son, Seon Kyoung; Kim, Bong Soo; Lee, Chun-Young; Lee, Joong Suk; Cho, Jeong Ho; Ko, Min Jae; Lee, Doh-Kwon; Kim, Honggon; Choi, Dong Hoon; Kim, Kyungkon (ELSEVIER, 2012)
Two low band gap copolymers (PQTDPP and PQTVTDPP) having quaterthiophene (QT) or bithiophene-vinylene-bithiophene (QTVT) as donor unit and diketopyrrolopyrrole (DPP) as acceptor unit have been synthesized via Stille cross-coupling polymerization. The polymers showed high thermal stability and broad light absorption with optical band gaps around 1.3 eV. Cyclic voltammetry measurements revealed that the HOMO and LUMO energy levels of QT and DPP copolymer (PQTDPP) were found to be -5.19 and -3.64 eV, respectively and those of PQTVTDPP -5.05 and -3.66 eV, respectively. X-ray diffraction patterns showed highly crystalline phase in the PQTDPP film and nearly amorphous in the PQTVTDPP film. This dramatic difference in crystallinity was attributed to the structural isomerization around vinyl groups in the PQTVTDPP polymer. Field-effect transistor measurement revealed that the PQTDPP showed high hole mobility of 0.06 cm(2)/Vs and on/off ratio of 106 while the PQTVTDPP showed hole mobility of 3.57 x 10(-4) cm(2)/Vs and on/off ratio of 10(5), which is consistent with X-ray diffraction results. Photovoltaic devices were also fabricated using polymer:PCBM blends in the structure of ITO/PEDOT:PSS/blend/Al. The PQTDPP devices exhibited an open circuit voltage (V-oc) of 0.58 V, a short circuit current (J(sc)) of 7.16 mA/cm(2), a fill factor (FF) of 0.55 and a power conversion efficiency (PCE) of 2.28%, and the PQTVTDPP devices exhibited an V-oc of 0.50 V, a J(sc) of 7.60 mA/cm(2), a FF of 0.51 and a PCE of 1.97% under AM 1.5 illumination. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPEN-CIRCUIT VOLTAGE; HETEROJUNCTION SOLAR-CELLS; PHOTOCURRENT GENERATION; CHARGE-TRANSPORT; EFFICIENCY; METHANOFULLERENE; POLYTHIOPHENE; TRANSISTORS; DEPENDENCE; ELECTRON